Comparison Between High- and Low-Intensity Static Stretching Training Program on Active and Passive Properties of Plantar Flexors - Nakamura, Masatoshi; Yoshida, Riku; Sato, Shigeru; Yahata, Kaoru; Murakami, Yuta; Kasahara, Kazuki; Fukaya, Taizan; Takeuchi, Kosuke; Nunes, João Pedro; Konrad, Andreas (Frontiers in Physiology, 2021)
The purpose of this study was to compare two static stretching (SS) training programs at high-intensity (HI-SS) and low-intensity (LI-SS) on passive and active properties of the plantar flexor muscles. Forty healthy young men were randomly allocated into three groups: HI-SS intervention group (n = 14), LI-SS intervention group (n = 13), and non-intervention control group (n = 13). An 11-point numerical scale (0–10; none to very painful stretching) was used to determine SS intensity. HI-SS and LI-SS stretched at 6–7 and 0–1 intensities, respectively, both in 3 sets of 60 s, 3×/week, for 4 weeks. Dorsiflexion range of motion (ROM), gastrocnemius muscle stiffness, muscle strength, drop jump height, and muscle architecture were assessed before and after SS training program. The HI-SS group improved more than LI-SS in ROM (40 vs. 15%) and decreased muscle stiffness (−57 vs. −24%), while no significant change was observed for muscle strength, drop jump height, and muscle architecture in both groups. The control group presented no significant change in any variable. Performing HI-SS is more effective than LI-SS for increasing ROM and decreasing muscle stiffness of plantar flexor muscles following a 4-week training period in young men. However, SS may not increase muscle strength or hypertrophy, regardless of the stretching discomfort intensity.